Effects of oregano (Lippia origanoides) essential oil supplementation on the performance, egg quality, and intestinal morphometry of Isa Brown laying hens - Swanny Y. Ramirez; Lina M. Peñuela-Sierra; Maria A. Ospina (Veterinary World, 2021)
Background and Aim: The use of antibiotics as growth promoters in the feed of poultry, has contributed to an increase in the antimicrobial resistance of foodborne pathogens worldwide. Hence, the development of new effective alternatives to antibiotics that do not hinder productivity is imperative. For this, the aim of the present study was to determine whether oregano essential oil (OEO) extracted from Lippia origanoides is a suitable alternative to growth-promoting antibiotics (GPAs) for improving the performance, egg quality, and intestinal morphometry of ISA Brown laying hens.